"DELIVER AFRICA FROM DEBTS": Good Governance Alone is not Enough to Save the Continent From Debt Onslaught. (September 2021) - Kinyondo, Abel; Pelizzo, Riccardo; Byaro, Mwoya
The present article analyzes the debt–economic growth nexus in African countries while controlling for the impact of good governance indicators. In contrast to a long tradition of scholarship that has consistently suggested that government debt has a detrimental impact on economic growth in sub-Saharan Africa, recent studies have actually shown that government debt, when coupled with improvements in the quality of government, is actually a driver of economic growth. By analyzing an original dataset that covers the 2002–15 period and additional debt–economic growth data going up to the year 2020, we are able to suggest three conclusions. First, in the absence of debt, good governance matters in improving economic growth. Second, some dimensions of governance are better predictors of economic performance than others—as the "good enough governance" literature has in recent years suggested. Third, under no circumstances is debt government growth beneficial for the economic performance of African countries. Building on this evidence, we suggest that the COVID-19 pandemic—which has already slowed down African economies and increased their debt exposure—may prevent African countries from making greater progress along the developmental path.